15th ICEEE 2024 Online International Annual Conference, 2024 november 21–22. Óbudai Egyetem: Global Environmental Development & Sustainability: Research, Engineering & Management - Centeri, Csaba (JOURNAL OF LANDSCAPE ECOLOGY, 2024)
-